Independence, Democracy and Institutional Choices - Feijó, Rui Graça (2013)
This paper proposes to celebrate the 10th anniversary of the independence of Timor-Leste by focusing on two controversies that marked the period before its proclamation and whose consequences extend into the present. The first one deals with the “road map to Independence” and comprises the debate on the best process to elaborate a Constitution. It is intertwined with the problem of the extent to which Timorese ought to participate in the critical decisions of the transitional period, conducted under the aegis of the United Nations. The second impinges on the choice of its system of government and its impact on the consolidation of democracy. This section discusses the relevant literature on semi- presidentialism to frame a comparative perspective to events in Timor-Leste and shows the historical evolution of the process of constitutional design and the debates it involved. Finally, this essay proposes to look at those critical choices as a function of the history of Timor-Leste since 1975 and the political balance of forces rather than derived from theoretical principles.